(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article outlines linguistic nature of abbreviation phenomenon in military vocabulary of Ukrainian language. The mechanism of formation of abbreviation in the names of weapon, accoutrements and military installations was determined. The semantic and functional particularities of abbreviations of various types were analyzed.